The fallout of war : the regional consequences of the conflict in Syria - Onder, Harun (World Bank Group, 2020)
The people of the Mashreq have seen more than their share of deaths, economic losses, and instability over the past decade. As the decade-long conflict in the Syrian Arab Republic created new challenges and worsened the existing ones, economic activity declined, labor markets deteriorated, and poverty increased. These trends would overwhelm even the most advanced economies in the world. This publication identifies the impact of the Syrian conflict on economic and social outcomes in Iraq, Jordan, and Lebanon. It combines a large number of data sources, statistical approaches, and a suite of economic models to isolate the specific impact of the Syrian conflict from that of global and regional factors, and it explicitly analyzes the mechanisms through which such an impact is manifested. The analysis suggests that a persistent short-termism in policy making has so far propagated the shock emanating from the Syrian conflict, which led to costly and ineffective service provision, lost economic opportunities, and underfunded programs. The report advocates for a fundamental shift from the short-term mitigation policies to a medium-term regional strategy to address pertinent structural problems. Moreover, as the countries in the Mashreq look toward recovery, a policy approach that takes into account the region's interconnectedness and seeks to build on it provides better prospects for the people. Such a regional approach that addresses cross-boundary issues-- including migration, trade, and infrastructure-- will require local, regional, and international commitments.